2003
DOI: 10.1002/pits.10105
|View full text |Cite
|
Sign up to set email alerts
|

Safe Schools/Healthy Students initiative: Pinellas County, Florida

Abstract: The Safe Schools/Healthy Students (SS/HS) Initiative in Pinellas County, FL, emerged as a part of a broader local effort to implement creative educational and mental health programs to support children and families. This initiative focused on capacity building, prevention, and intervention efforts and comprehensive evaluation to address the barriers to learning and enhance healthy development. This article describes Pinellas County's plan, and highlights the instrumental roles played by school psychologists, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Quite tentatively, results support current best practice research on interventions that target building protective factors, such as increasing social competence and promoting feelings of belongingness to the school (Armstrong, Massey, Boroughs, Bailey, & Lajoie, 2003; Baker, Dilly, Aupperlee, & Patil, 2003; Gettinger, 2003; Osterman, 2000). For instance, research on prevention and wellness models has found that schools that function as models of healthy environments and promote social competence yield more positive effects, such as greater academic performance and more positive peer interactions (Armstrong et al, 2003; Baker et al, 2003; Gettinger, 2003; Osterman, 2000). In particular, Osterman described key factors associated with belongingness.…”
Section: Discussionsupporting
confidence: 67%
“…Quite tentatively, results support current best practice research on interventions that target building protective factors, such as increasing social competence and promoting feelings of belongingness to the school (Armstrong, Massey, Boroughs, Bailey, & Lajoie, 2003; Baker, Dilly, Aupperlee, & Patil, 2003; Gettinger, 2003; Osterman, 2000). For instance, research on prevention and wellness models has found that schools that function as models of healthy environments and promote social competence yield more positive effects, such as greater academic performance and more positive peer interactions (Armstrong et al, 2003; Baker et al, 2003; Gettinger, 2003; Osterman, 2000). In particular, Osterman described key factors associated with belongingness.…”
Section: Discussionsupporting
confidence: 67%
“…All sites reviewed in this special issue involved coordinated school-community service delivery structures. Pinellas County, Florida (Armstrong, Massey, Boroughs, Bailey, & LaJoie, 2003), Cicero, Illinois (Tellen, Maher, & Pesce, 2003), and Hays, Kansas (Paige, Kitzis, & Wolfe, 2003) received considerable ongoing support from school psychologists who were actively involved in writing and implementing the projects. The projects in Salinas, California (Elizondo, Feske, Edgull, & Walsh, 2003), Riverside, California (Guerra & Williams, 2003) and Tyone, Pennsylvania (Welsh, Domitrovich, Bierman, & Lang, 2003) relied more on outside clinical professionals, consultants, and agencies to provide programs in the schools.…”
Section: Enhancing the Mental Health Of Children And Familiesmentioning
confidence: 99%
“…Their plan developed a public health model of violence prevention within the school system and the surrounding communities (Armstrong, Massey, Boroughs, Bailey, & LaJoie, 2003). The plan relied heavily on the provision of services by teams of professionals drawn from the school district as well as from community-based service providers under contractual agreements.…”
mentioning
confidence: 99%